If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2=-4x+2(x+8)
We move all terms to the left:
-2-(-4x+2(x+8))=0
We calculate terms in parentheses: -(-4x+2(x+8)), so:We get rid of parentheses
-4x+2(x+8)
We multiply parentheses
-4x+2x+16
We add all the numbers together, and all the variables
-2x+16
Back to the equation:
-(-2x+16)
2x-16-2=0
We add all the numbers together, and all the variables
2x-18=0
We move all terms containing x to the left, all other terms to the right
2x=18
x=18/2
x=9
| -2f=-8−f | | -21=-3+3x | | 2x+4(-4)=16 | | 5^9x-1=25 | | 10y+4X=120 | | 12x−-13x−8x−6x−20x=-18 | | 3^9x-1=9 | | -3x^2+30x-4=0 | | 1n+2=6-6n | | x2^-25=0 | | -2(u+2)=3u-6+2(5u+6) | | 2x+4-2=16 | | 14=2u-10 | | x4-81=0 | | -6u+30=3(u+4) | | 2(4a+1)−7a=8−5 | | 8x^2+15x=0 | | 7/2x+1/2x=5+9/2 | | -16x-7=26x-7(6x-7) | | 2(v-1)=-9v-24 | | y=14+19 | | 473.10=38(x+2.45) | | 3x2+6x-72=0 | | 4y=6y-6 | | 9x-4/x=2 | | 3-9=7x-6x+6 | | 24m+20m-12=164 | | 31(x+2.45)=509.95 | | 8c–6=10 | | x^2-9x+48=0 | | 3.25+0.5x+113+56x=511/12 | | 2x=3x^2+1 |